2010
DOI: 10.1186/1742-2094-7-62
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ signaling in the brain increases with aging and signals to astrocytes and innate immune cells in the weeks after stroke

Abstract: BackgroundTGFβ is both neuroprotective and a key immune system modulator and is likely to be an important target for future stroke therapy. The precise function of increased TGF-β1 after stroke is unknown and its pleiotropic nature means that it may convey a neuroprotective signal, orchestrate glial scarring or function as an important immune system regulator. We therefore investigated the time course and cell-specificity of TGFβ signaling after stroke, and whether its signaling pattern is altered by gender an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
166
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(188 citation statements)
references
References 37 publications
(51 reference statements)
10
166
1
1
Order By: Relevance
“…A major contributor of tissue fibrosis is activation of TGF-␤1 signaling, which is amplified during aging (21). There are also reports showing that TGF-␤ signaling could be suppressed by calorie restriction (CR) (22).…”
Section: Resultsmentioning
confidence: 99%
“…A major contributor of tissue fibrosis is activation of TGF-␤1 signaling, which is amplified during aging (21). There are also reports showing that TGF-␤ signaling could be suppressed by calorie restriction (CR) (22).…”
Section: Resultsmentioning
confidence: 99%
“…33 The signals that maintain this chronic neuroinflammation have not been fully established, but TGFb1 is a strong candidate. TGFß1 expression is both delayed and prolonged after brain injury 8,34,35 and several studies have shown that it can stimulate neuroinflammation within the CNS. 14,36 Moreover, over-expression of TGFb1 in the CNS of The integrated optical density (IOD) was determined for MBP and GFAP immunoreactivity in the neocortex, striatum and the corpus callosum (CC) from ipsilateral (IL) and contralateral (CL) hemispheres as well as from shamoperated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Hematoxylin and eosin staining and immunostaining were performed as described using standard techniques on PFA-fixed 40 m coronal brain sections (Doyle et al, 2010). Primary antibodies were against B220 (biotinylated, 1:500; BD Biosciences, 553085), CD11c (1:500; Abcam, ab33483), IgG (biotinylated, 1:1000; Vector, BA-2000), CD3 (1:500; BD Biosciences, 550277), MHCII (I-A/I-E, 1:500; BD Biosciences, 553621), CD68 (1: 1000; Serotec, MCA1957), and Iba1 (1:1000; Wako, .…”
Section: Methodsmentioning
confidence: 99%